Role of Innovations to Mitigate CO2e: Theory and Evidence for European Economies - Umar Farooq M.; Amin A.; Peng S.; I??k C.; Aqdas R.; Akbar M.; Sabahat G.; Ongan S. (MDPI, 2024)
Even though numerous researchers have analyzed the factors of carbon emissions, technological innovations linear and non-linear effects on carbon emissions have not been thoroughly examined in the energyenvironment literature with the Environmental Kuznets Curve framework for European economies. For this purpose, this study has employed linear and non-linear autoregressive distributed lagged models, the novel bounds testing methodologies of dynamic simulations. Renewable energy and resident and non-resident patents are the indicators of technological innovations. The findings of this study demonstrate a significant negative association of renewable energy use and technological innovation with carbon emissions, while economic growth, non-renewable energy, and urbanization have depicted a positive relationship. These findings confirm the validity of the Environmental Kuznets hypothesis for the sampled countries. It is suggested that research and development facilities are required to mitigate environmental pollution by using innovation and discouraging more use of coal in electricity generation. This study also provides policymakers with particular statistics on sector-based renewable energy initiatives, highlighting the greenhouse gas impacts in European countries. 2023 by the authors.